Analisis Tingkat Potensi Resiko Kecelakaan Kerja Menggunakan Metode Failure Mode And Effect Analysis (FMEA) di PT. Duta Wira Utama - Muhibb Zulfa; Ari Zaqi Al-Faritsy (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
PT Duta Wira Utama is an experienced manufacturing company in the engineering field and uses various machines such as drilling, lathe, Milling, and plasma cutting machines in its production process. These activities have a high risk of occupational accidents, caused by human error, environmental conditions, and lack of safety education. Two work accidents were recorded in the last two years, namely being pinched by a lathe in 2022 and being hit by a tool blade in 2021, which had an impact on reducing productivity and temporarily stopping the production process. This study aims to identify potential risks of work accidents and analyze the level of worker awareness of work safety. The method used is FMEA (Failure Mode and Effect Analysis) to identify potential risks and Fishbone Diagram to analyze the causes of low work safety awareness. The FMEA results show 22 potential workplace accidents, while the Fishbone Diagram reveals five main factors that affect safety awareness, namely machinery/equipment, materials, people, methods, and environment. The results show that to improve work safety and reduce the risk of accidents at work sites, an in-depth evaluation of these elements is required